Analysis of Improving Community Services Through Organizational Communication in the Yogyakarta Licensing Service - Ika Widiastuti; Pandu Adi Cakranegara (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2021)
Organizational communication serves as a means to build employee motivation so that public services can develop more advanced. Effective communication is vital for employee cooperation to achieve organizational goals. The Jogjakarta Licensing Service commits to public service, as evidenced by the number of awards. The purpose of the research is to know the forms of communication applied by the Yogyakarta Licensing Service to improve public services and understand the concepts and theories of organizational communication and public services. The research method used is descriptive qualitative. The results show that the Yogyakarta Licensing Service's organizational communication consists of upward communication, downward communication, vertical communication, horizontal communication, and formal and informal communication. Komunikasi organisasi berfungsi sebagai sarana untuk membangun motivasi pegawai agar pelayanan publik dapat berkembang lebih maju. Komunikasi yang efektif sangat penting bagi kerja sama karyawan untuk mencapai tujuan organisasi. Dinas Perizinan Yogyakarta berkomitmen terhadap pelayanan publik, terbukti dengan banyaknya penghargaan. Tujuan dari penelitian ini adalah untuk mengetahui bentuk-bentuk komunikasi yang diterapkan oleh Dinas Perizinan Yogyakarta untuk meningkatkan pelayanan publik serta memahami konsep dan teori komunikasi organisasi dan pelayanan publik. Metode penelitian yang digunakan adalah deskriptif kualitatif. Hasil penelitian menunjukkan bahwa komunikasi organisasi Dinas Perizinan Yogyakarta terdiri dari komunikasi ke atas, komunikasi ke bawah, komunikasi vertikal, komunikasi horizontal, dan komunikasi formal, dan informal.